2014
DOI: 10.1177/1358863x14554034
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of circulating chemokine (C-C motif) ligand 2 in patients with chronic ischemia threatening the lower extremities

Abstract: The role of chemokine (C-C motif) ligand 2 (CCL2) in peripheral artery disease is unclear. We measured the difference between serum and plasma levels of CCL2 in patients with chronic ischemia threatening the lower extremities following the observation that atypical chemokine receptors in blood and tissue cells may prevent CCL2 from entering the circulation and consequently modulate its function of attracting monocytes to the site of lesion. To identify the influence of CCL2, we compared the patients' values to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Reports indicate that human carotid plaques express galectin-3 in smooth muscle cells, especially in macrocalcified areas, where it co-localizes with alkaline phosphatase [16]. Of note from an early study from our group is the observation of calcium deposition in the media of arteries from PAD patients; a distinct and frequent finding in affected arteries [32]. In the same study, we reported an increase in CD68-positive cells in diseased arteries; the conclusion drawn is that, under certain stimuli, arterial smooth muscle cells can shift their phenotypes to a macrophage-cell state [33].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Reports indicate that human carotid plaques express galectin-3 in smooth muscle cells, especially in macrocalcified areas, where it co-localizes with alkaline phosphatase [16]. Of note from an early study from our group is the observation of calcium deposition in the media of arteries from PAD patients; a distinct and frequent finding in affected arteries [32]. In the same study, we reported an increase in CD68-positive cells in diseased arteries; the conclusion drawn is that, under certain stimuli, arterial smooth muscle cells can shift their phenotypes to a macrophage-cell state [33].…”
Section: Discussionmentioning
confidence: 93%
“…Control tissue samples were processed identically to the test samples, except that the primary antibodies were omitted from the incubation. The immunohistochemical expressions of CD68 antigen and α-actin were used as markers of macrophages and smooth muscle cells, respectively, and analyzed as previously reported [32,44]. …”
Section: Methodsmentioning
confidence: 99%
“…In agreement with this hypothesis, several articles have shown a decrease in the levels of CCL2 and CXCL8 (IL-8) in serum from persons with the rs12075 G allele [26,39,40,41]. Besides, the rs12075 G allele has also been related with low CCL2 levels in patients with chronic inflammatory diseases such as ischemia of the lower extremities [42] and obesity [43], as well as low leukocyte counts in African people [44].…”
Section: Discussionmentioning
confidence: 78%
“…Participants with diabetes mellitus were excluded to avoid metabolic bias and to limit variability. Further clinical details on the inclusion and exclusion criteria have been previously described [20].…”
Section: Isolation and Preparation Of Biological Samplesmentioning
confidence: 99%